2018
DOI: 10.1080/16583655.2018.1514147
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and computational study of gumexudatesfromCanarium schweinfurthiias green corrosion inhibitor for mild steel in HCl solution

Abstract: The inhibition efficiency of the corrosion on mild steel in acid by Canarium schweinfurthii (CS) gum as inhibitor has been studied using chemical techniques (thermometric, gasometric, spectrophotometric and weight loss) and electrochemical techniques (electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PDP)). Scanning Electron Spectroscopy (SEM) was used to examine the surface morphology of mild steel samples both in the presence and absence of inhibitors at optimum conditions. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Tizhe and coworkers [51] reported that GETM have a variety of phytochemicals like alkaloids, saponins, flavonoids, tannins and terpenes among others. These compounds are rich in conjugated aromatic structures and contain heteroatoms with free electron pairs that are available to form bonds with the metal surface [52]. It is therefore, pertinent to say that the adsorption of these compounds onto mild steel surface is responsible for the corrosion inhibition effect.…”
Section: Mechanism Of Inhibitionmentioning
confidence: 99%
“…Tizhe and coworkers [51] reported that GETM have a variety of phytochemicals like alkaloids, saponins, flavonoids, tannins and terpenes among others. These compounds are rich in conjugated aromatic structures and contain heteroatoms with free electron pairs that are available to form bonds with the metal surface [52]. It is therefore, pertinent to say that the adsorption of these compounds onto mild steel surface is responsible for the corrosion inhibition effect.…”
Section: Mechanism Of Inhibitionmentioning
confidence: 99%
“…Plant materials are promising green corrosion inhibitors for steel as revealed by several studies [11][12][13][14][15]. Plant materials are not only organic but eco-friendly and pose less health concerns in respect of their toxic effects to man and animals compared to inorganic corrosion inhibitors like the salts of vanadium and chromium, and some toxic synthetic organic compounds [16].…”
Section: Introductionmentioning
confidence: 99%
“…The nitrogen found in the briquettes is attributed to the fuel-N found in charcoal fines (Glarborg et al, 2003) as well as nitrogen-containing compounds in the Canarium Schweinfurthii resin (Ameh, 2018). For oxygen, LSD showed that the difference of the means was not significant for briquettes B30/B25, B35/B25 and B35/B30.…”
Section: Ultimate Analysis Higher Heating Value and Energy Density Of...mentioning
confidence: 91%
“…The peak emissions of SO2, NO2, and CO2 from the briquettes met this standard. The NO x found in the briquettes is attributed to the fuel-N found in charcoal fines (Glarborg et al, 2003) as well as nitrogencontaining compounds in the Canarium Schweinfurthii resin (Ameh, 2018). The S๐‘‚ 2 is attributed to the Sulphur in the charcoal fines (Deac et al, 2016).…”
Section: Response Surface Plotsmentioning
confidence: 95%
See 1 more Smart Citation